STING Operation at the ER/Golgi Interface - Taguchi, Tomohiko; Mukai, Kojiro; Takaya, Eiko; Shindo, Ruri (Frontiers in Immunology, 2021)
DNA is present in the nucleus and mitochondria of eukaryotic cells. There are, however, certain instances in which DNA emerges in the cytosol. The two major sources of cytosolic DNA are self DNA that is leaked out from the nucleus or mitochondria, and non-self DNA from DNA viruses. The cytosolic DNA triggers the host immune response. Recent studies have identified two key molecules, cyclic GMP-AMP (cGAMP) synthase (cGAS) and stimulator of interferon genes (STING) in this immune response. STING is an endoplasmic reticulum (ER) protein. After STING binding to cGAMP, STING exits the ER and translocates to the Golgi, where STING triggers the type I interferon- and proinflammatory responses through the activation of interferon regulatory factor 3 (IRF3) and nuclear factor-kappa B (NF-κB). STING also activates other cellular responses including cell senescence, autophagy, and cell death. In this review, we focus on emerging issues regarding the regulation of STING by membrane traffic, with a particular focus on the retrograde membrane traffic from the Golgi to the ER. The retrograde membrane traffic is recently shown by us and others to be critical for silencing the STING signaling pathway and the defect in this traffic underlies the pathogenesis of the COPA syndrome, a monogenic autoinflammatory disease caused by missense mutations of coatomer protein complex subunit α (COP-α).